1991
DOI: 10.1002/clc.4960140211
|View full text |Cite
|
Sign up to set email alerts
|

Once‐daily pravastatin in patients with primary hypercholesterolemia: A dose‐response study

Abstract: Summary:This multicenter, double-blind, placebocontrolled study was conducted to evaluate dose-response effects and safety of once-daily administration of pravastatin, a new inhibitor of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase. Pravastatin 5, 10, 20, 40 mg or placebo was administered at bedtime to 150 patients with primary hypercholesterolemia inadequately controlled on a low-fat, low-cholesterol (AHA Phase I) diet. After 8 weeks of treatment, pravastatin produced dose-dependent reductions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
16
0
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 12 publications
7
16
0
2
Order By: Relevance
“…For example, the percentage reduction in LDL cholesterol from baseline was similar, about 30%, in both groups. LDL responses of a similar magnitude have been observed in clinical trials with the same pravastatin dose (40 mg/day) (73,75,76). Although our study had sufficient statistical power to detect only a large difference in lipid response between the two groups (60), the results suggest that the SLCO1B1 polymorphism does not play a major role in non-response to pravastatin.…”
Section: Effectiveness Of Pravastatinsupporting
confidence: 76%
See 1 more Smart Citation
“…For example, the percentage reduction in LDL cholesterol from baseline was similar, about 30%, in both groups. LDL responses of a similar magnitude have been observed in clinical trials with the same pravastatin dose (40 mg/day) (73,75,76). Although our study had sufficient statistical power to detect only a large difference in lipid response between the two groups (60), the results suggest that the SLCO1B1 polymorphism does not play a major role in non-response to pravastatin.…”
Section: Effectiveness Of Pravastatinsupporting
confidence: 76%
“…However, it appears that the doseYresponse curves for statins are steepest with doses below the lower limit of the recommended dose range (which is 10 mg/day for pravastatin), being shallow across their usual dose ranges (73,76,77). For example, clinical studies found little difference in the LDL response to pravastatin between daily doses of 20 and 40 mg (75,76). Finally, it should be noted that the relationship between statin-induced intracellular inhibition of cholesterol synthesis and the cholesterollowering efficacy is rather complex (74,78Y80).…”
Section: Effectiveness Of Pravastatinmentioning
confidence: 96%
“…Serum cholesterol levels have not been reported to show rebounds between day 4 and 8 of routine statin administration when indicated for hypercholesterolemia. 16,17 The cholesterol rebounds observed in our study might reflect (1) unique effects on cholesterol homeostasis of the Ida-HDAC chemotherapy, (2) decreased uptake of cholesterol because of the elimination of the cholesterol-avid leukemic blasts, or (3) the release back into the serum of previously imported cholesterol by the leukemia cells which were killed by the Ida-HDAC chemotherapy. Our previous laboratory studies suggest that the cholesterol levels needed by leukemia cells for survival are quite variable, as is their relative dependence on new cholesterol synthesis versus import.…”
Section: Discussionmentioning
confidence: 79%
“…Unable to ascertain actual numbers for cardiac death and myocardial infarction Jones 1991 Length of treatment is only eight weeks KLIS 2000 Not randomised Lemaitre 2002 Cohort study McGrae McDremott 2003 Subjects were not randomised to statins or no statins Mohler 2003 Patients recruited had peripheral arterial disease Muldoon 1997 Treatment length is only six months Nephrotic Syndrome Study Treatment length was only nine months Ohta 2000 Treatment length is only six months Oi 1997 No placebo or control group Ormiston 2003 Not an RCT - all participants were given statins Pitt 1999 No Placebo - Statins versus Angioplasty POSCH 1990 Statins were not used Pravastatin Multi 1993 Treatment length was only 26 weeks PROSPER 2002 More than 10% of the participants had CVD Sprecher 1994 Treatment length is only 24 weeks Stein 1997 Treatment length is only four weeks Su 2000 Treatment length is only six months Tanaka 2001 Treatment length is only 12 weeks …”
Section: Characteristics Of Included Studies [Ordered By Study Id]mentioning
confidence: 99%